2018
DOI: 10.1177/1934578x1801300127
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Volatile Fraction from Inflorescences and Leaves of Dendrobium moschatum (Orchidaceae)

Abstract: The volatile fractions from fresh inflorescences and leaves of Dendrobium moschatum (Buchanan-Hamilton) Swartz (Orchidaceae) were isolated by steam distillation with a yield of 0.498% and 0.041% (weight/fresh weight basis), respectively. From GC/FID and GC/MS analyses, coumarin was identified to be the most abundant constituent and quantified as 48.8% and 47.8% of the total volatiles from inflorescences and leaves, respectively. Hydrocarbons, ketones, esters, acids and aldehydes were also detected. Long chain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
0
12
1
Order By: Relevance
“…Palmitic acid was the only compound shared by all the five taxa examined. This molecule is frequently found in the volatilome of several plant species (Orchidaceae included) [ 23 , 35 , 42 ], and also in other organisms; we observed that it was relatively abundant in D. chrysanthum (13%), followed by D. harveyanum (7.52%) and D. wardianum (5.76%), while in the remaining two species it was less represented.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Palmitic acid was the only compound shared by all the five taxa examined. This molecule is frequently found in the volatilome of several plant species (Orchidaceae included) [ 23 , 35 , 42 ], and also in other organisms; we observed that it was relatively abundant in D. chrysanthum (13%), followed by D. harveyanum (7.52%) and D. wardianum (5.76%), while in the remaining two species it was less represented.…”
Section: Discussionmentioning
confidence: 63%
“…High content of volatile esters has been linked with the strong flavor of the “snow chrysanthemum” cultivar of Coreopsis by Kim et al (2020) [ 44 ]. In D. moschatum , a putative role as semiochemicals involved in pollinator attraction has been hypothesized for methyl and ethyl esters by Robustelli della Cuna et al (2017) [ 23 ]. According to da Silva et al (1999) and Cseke et al (2007), terpenes are more abundant in flower VOCs of species pollinated by food-seeking bees [ 45 , 46 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of hydrocarbons as allelochemicals is associated with epicuticular wax chemistry playing an important role in plant/herbivore interactions. Saturated alkanes exerted an interesting, although limited, activity in pollinator deception in different floral species [25,29,30,31].…”
Section: Discussionmentioning
confidence: 99%
“…A portion of the essential oil from each sample was placed onto a glass column (7 × 30 mm) of silica gel 60, 230–400 mesh (Merck, Milano, Italy), preconditioned with pentane [29]. The non-polar fraction was eluted with 2 mL of pentane and used for the determination of double bond position in alkenes by alkylthiolation according to reported method [50].…”
Section: Methodsmentioning
confidence: 99%